(untitled) (Hoboken, NJ, 2013)
The importance of the life's work of mutual fund pioneer and investing legend John C. BogleThe Man in the Arena offers the essence of John C. Bogle's thinking and the meaning of his life's work, which transformed individual investing to benefit tens of millions of investors. Through Bogle's own words--as well as the voices of others whose hearts and minds he touched--the book touches on topics he cares about most deeply: Vanguard, indexing, corporate governance, and a fiduciary society. From Vanguard shareholders to true giants in finance, one cannot read their words without being struck by their sheer intensity. Bogle's parade of admirers is passionate. It is led by, arguably, the two most acclaimed leaders of our day--in the world of investing and the public life of the world--Warren Buffett and President Bill Clinton.The book is a first take at putting Bogle's life work into a broader context. It includes some of Bogle's classic essays and leads to an agenda of reform Bogle feels is essential to preserve our democratic republic. It features insight on the man from such commentators as Arthur Levitt, Burton Malkiel, Paul Volcker, and many more. Features wisdom and commentary on the career and life of legendary investor John C. Bogle Presents a summary of Bogle's prominent and successful career, as well as his investing strategies Includes commentary from a Who's Who of top investors
Keywords: Investments,Đầu tư; United States,Hoa Kỳ